Remote antemortem inspection at slaughter in Sweden - Hansson, Elise; Medin, Ingrid; Almqvist, Viktor; Boqvist, Sofia; Vågsholm, Ivar; Östberg, Rebecka; Kautto, Arja Helena (Frontiers in Food Science and Technology, 2025)
Domesticated and farmed animals that are slaughtered commercially for human consumption undergo antemortem inspections (AMIs) by official veterinarians to comply with the legislation of the European Union. Small-capacity abattoirs and game-handling establishments are often located in remote areas and have high resource demand for onsite control. This study aimed to study the feasibility of remote AMIs performed by veterinarian raters with limited prior experience in AMI and to evaluate the user experiences assessed by raters having lifelong experience with digital devices in their daily lives. The present study was performed over 4 d (18 sessions) at a large-capacity abattoir slaughtering pigs and another 4 d (four sessions) at a small-capacity abattoir slaughtering cattle and sheep. The interrater variability between two raters (one technical support person conducting onsite AMI and one remote rater conducting remote AMI over a live video feed) was assessed, and the raters scored their user experiences for each session. A total of 4,032 pigs, 39 cattle, and 10 sheep were inspected over the 22 sessions. We observed high levels of overall agreement (99.4%), Cohen’s kappa (0.920; 95% confidence interval (CI): 0.888–0.953), and prevalence- and bias-adjusted kappa (0.989; 95% CI: 0.983–0.993) between the onsite and remote AMIs for the large-capacity abattoir. These results were also supported by the McNemar test (χ2 = 0.375; df = 1; p = 0.54). The sample size at the small-capacity abattoir was low (N = 49), and marginal rating frequencies were different, for which the Fisher’s exact test showed statistical differences (p < 0.001) between the onsite and remote AMI results. The average user experience scores for all categories were rated as satisfactory or better. Consequently, remote AMI is a feasible and flexible option for official meat inspections in slaughter, provided the inspectors are trained and aligned in their assessments of AMI findings.